Lipid-altering efficacy of ezetimibe plus statin and statin monotherapy and identification of factors associated with treatment response: A pooled analysis of over 21,000 subjects from 27 clinical trials - Morrone, Doralisa; Weintraub, William S.; Toth, Peter P.; Hanson, Mary E.; Lowe, Robert S.; Lin, Jianxin; Shah, Arvind K.; Tershakovec, Andrew M. (Atherosclerosis, 2012)
Patients with dyslipoproteinemia constitute the largest risk group for development of atherosclerosis and cardiovascular disease (CVD). Despite extensive statin use, many patients with CVD risk do not achieve guideline-recommended low-density lipoprotein cholesterol (LDL-C) targets. This pooled analysis of 27 previously published clinical trials conducted between 1999 and 2008 evaluated the lipid-altering efficacy and factors related to treatment response of ezetimibe combined with statin and statin monotherapy. Patient-level data were combined from double-blind, placebo-controlled or active comparator studies randomizing adult subjects to ezetimibe 10mg plus statin (n=11,714) versus statin alone (n=10,517) for 6–24 weeks (mean=9 weeks). Association of factors with treatment response, percent change from baseline LDL-C and other lipids, and attainment of guideline-recommended lipid and lipoprotein targets were evaluated. Higher baseline LDL-C, diabetes mellitus, Black race, greater age, and male gender were associated with small but significantly greater percent reductions in LDL-C regardless of treatment. Treatment influenced efficacy, with ezetimibe plus statin producing significantly greater reductions in LDL-C, total-cholesterol, non-HDL-C, ApoB, triglycerides, lipid ratios, hs-CRP; significantly larger increases in HDL-C and ApoA1; and significantly higher achievement of LDL-C (<70mg/dl, <100mg/dl), non-HDL-C (<100mg/dl, <130mg/dl), and ApoB (<80mg/dl, <90mg/dl) targets than statin monotherapy at statin potencies compared (p<0.0001 for all). Differential treatment effects were seen with first-/second-line therapy and statin potency. These results suggest that patient characteristics have a limited influence on response to lipid-lowering therapy and demonstrate the consistent treatment effect of ezetimibe combined with statin and statin monotherapy across a diverse patient population.